Proyecto De Negocio Internacional Para La Exportación De Aguacate Hass Desde Cundinamarca A Málaga España (2023)
In the Cundinamarca department, there is a significant production of Hass avocados; however, this production boasts remarkable technical characteristics in terms of quality. It has been in local distribution and sales for many years, yet it has also been the subject of efforts by the department's government to improve the quality of life for the producers.